Selected quality factors in the function of creating guests' satisfaction - Vujić Tamara; Vujić Milan; Zrnić Miloš; Gajić Tamara; Vukolić Dragan (Marketing (Beograd. 1991), 2022)
The quality of service is an ongoing problem of research in the world in all service sectors and dictates potential expectations among guests and their satisfaction. Pursuant to the problem and theoretical setting of similar research, the authors identified the quality factors of hotel service in Divčibare, to determine their impact on guest satisfaction. Methods used in research are descriptive and regressive analysis. The authors used a modified questionnaire from the author of Akbab (2006), for the international community. The survey was conducted during 2022, with a total sample of 442 respondents. The study showed that the material component of the hotel service has a positive impact on the loyalty of visitors to the hotel building, in relation to the intangible component. In addition, by observing the behaviour of guests, it is possible to respond to their demands and needs which are a major factor in creating loyalty.